2013
DOI: 10.1152/ajpregu.00189.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extraluminal ATP application on vascular tone and blood flow in skeletal muscle: implications for exercise hyperemia

Abstract: During skeletal muscle contractions, the concentration of ATP increases in muscle interstitial fluid as measured by microdialysis probes. This increase is associated with the magnitude of blood flow, suggesting that interstitial ATP may be important for contraction-induced vasodilation. However, interstitial ATP has solely been described to induce vasoconstriction in skeletal muscle. To examine whether interstitial ATP induces vasodilation in skeletal muscle and to what extent this vasoactive effect is mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 67 publications
(117 reference statements)
1
29
1
Order By: Relevance
“…In this light, the administration of a low dose of ATP to the muscle interstitium does not alter tissue blood flow in human limbs and even causes vasoconstriction of the rat gluteus maximus muscle microcirculation (Nyberg et al . 2013). This contrasts to the increases in limb deep tissue flow seen in the present study when the same dose of ATP was administered intraluminally (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this light, the administration of a low dose of ATP to the muscle interstitium does not alter tissue blood flow in human limbs and even causes vasoconstriction of the rat gluteus maximus muscle microcirculation (Nyberg et al . 2013). This contrasts to the increases in limb deep tissue flow seen in the present study when the same dose of ATP was administered intraluminally (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial ATP can induce vasoconstriction via P2X receptors on the smooth muscle cells or, alternatively, induce vasodilatation by acting on P2Y receptors on the endothelial cells (48). Animal experiments have suggested that the vasodilatory effect of interstitial ATP is stronger than its constrictive effect (93,313).…”
Section: Control Of Exercise Hyperemiamentioning
confidence: 99%
“…ATP has been proposed to play a role in skeletal muscle vasodilation (11-13) which is supported by its potent vasodilator capacity (20,22,34) and the observation that the concentration of this substance increases in the venous effluent of contracting skeletal muscle of young subjects (17,21). In contrast, ATP has been reported not to increase in venous plasma draining the exercising forearm of older subjects (17).…”
Section: We Recently Demonstrated That Inhibition Of Cgmp-binding Phomentioning
confidence: 99%
“…Since the first report on the hemodynamic response to exercise in older individuals in 1974 (42), evidence has accumulated for an insufficient blood flow to contracting skeletal muscle in aging (3,5,17,18,23,26,28,30,31). This altered regulation with aging could be related to a diminished ability for functional sympatholysis (10,20,36) and/or reduced efficacy of local vasodilator pathways (20,38,40).ATP has been proposed to play a role in skeletal muscle vasodilation (11-13) which is supported by its potent vasodilator capacity (20,22,34) and the observation that the concentration of this substance increases in the venous effluent of contracting skeletal muscle of young subjects (17,21). In contrast, ATP has been reported not to increase in venous plasma draining the exercising forearm of older subjects (17).…”
mentioning
confidence: 99%